2020
DOI: 10.1111/bph.15203
|View full text |Cite
|
Sign up to set email alerts
|

Repeated social defeat stress induces neutrophil mobilization in mice: maintenance after cessation of stress and strain‐dependent difference in response

Abstract: Background and Purpose Inflammation has been associated with stress‐related mental disturbances. Rodent studies have reported that blood‐borne cytokines are crucial for stress‐induced changes in emotional behaviours. However, the roles and regulation of leukocytes in chronic stress remain unclear. Experimental Approach Adult male C57BL/6N mice were subjected to repeated social defeat stress (R‐SDS) with two protocols which differed in stress durations, stress cycles, and housing conditions, followed by the soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
3
14
0
Order By: Relevance
“…Regarding the association of immune markers and social interaction, a recent study showed that repeated social defeat stress increased neutrophils and monocytes in the blood, and this increase may contribute to the development of social avoidance (Ishikawa et al, 2021). Additionally, NLR and MLR were significantly associated with cognitive performance in patients with major depressive disorder (Fourrier et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the association of immune markers and social interaction, a recent study showed that repeated social defeat stress increased neutrophils and monocytes in the blood, and this increase may contribute to the development of social avoidance (Ishikawa et al, 2021). Additionally, NLR and MLR were significantly associated with cognitive performance in patients with major depressive disorder (Fourrier et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effects of repeated social defeat (RSD) with social disruption (SDR) on DCs of the spleen and peripheral blood were compared in mice [ 256 ]. Both stress paradigms equally induced social avoidance in the same manner and caused a decrease in the proportion of DC subsets (cDC1 and cDC2) in the bone marrow of defeated animals.…”
Section: Dcs In Rodent Models Of Mood Disordersmentioning
confidence: 99%
“…Infiltration of neutrophils in the CNS, their adhesion and concomitant secretion can contribute to the development of inflammation and numerous neurological and neurodegenerative diseases, including MDD (Prinz and Priller, 2017;Kanashiro et al, 2020). Repetitive social defeat stress induces the mobilization of neutrophils in mice, which may contribute to the development of mental illness (Ishikawa et al, 2020). Genetic analysis revealed that MDD is associated with increased expression of innate immune and neutrophilrelated genes in peripheral blood (Wittenberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%